Design, synthesis and anti-mycobacterial evaluation of imidazo[1, 2-a]pyridine analogues. Issue 3 (2nd February 2022) - Khetmalis, Yogesh Mahadu; Chitti, Surendar; Umarani Wunnava, Anjani; Karan Kumar, Banoth; Murali Krishna Kumar, Muthyala; Murugesan, Sankaranarayanan; Chandra Sekhar, Kondapalli Venkata Gowri
Abstract : 34 imidazo[1, 2- a ]pyridine amides & sulfonamides are synthesized & evaluated for in vitro anti-TB activity against MTB H37Rv. IPA- 6 is most potent with MIC 0.05 μg mL −1 & 125 times active than ethambutol & docked to MTB enoyl acyl protein reductase. Abstract : Based on the molecular hybridization strategy, thirty-four imidazo[1, 2- a ]pyridine amides (IPAs) and imidazo[1, 2- a ]pyridine sulfonamides (IPSs) were designed and synthesized. The structures of the target compounds were characterized using 1 H NMR, 13 C NMR, LCMS, and elemental analyses. The synthesized compounds were evaluated in vitro for anti-tubercular activity using the microplate Alamar Blue assay against Mycobacterium tuberculosis H37Rv strain and the MIC was determined. The evaluated compounds exhibited MIC in the range 0.05–≤100 μg mL −1 . Among these derivatives, IPA- 6 (MIC 0.05 μg mL −1 ), IPA- 9 (MIC 0.4 μg mL −1 ), and IPS- 1 (MIC 0.4 μg mL −1 ) displayed excellent anti-TB activity, whereas compounds IPA- 5, IPA- 7 and IPS- 16 showed good anti-TB activity (MIC 0.8–3.12 μg mL −1 ). The most active compounds with MIC of <3.125 μg mL −1 were screened against human embryonic kidney cells to check their cytotoxicity to normal cells. It was observed that these compounds were nontoxic (SI value ≥66). The ADMET characteristics of the final compounds were also predicted in silico . Further, using the Glide module of Schrodinger software, a molecular docking study of IPA- 6 was carried out to estimate the binding pattern at the active site of enoyl acyl carrier protein reductase from Mycobacterium tuberculosis (PDB ; 4TZK ). Finally, molecular dynamics simulations were performed for 100 ns to elucidate the stability, conformation, and intermolecular interactions of the co-crystal ligand and significantly active compound IPA- 6 on the selected target protein. IPA- 6, the most active compound, was found to be 125 times more potent than the standard drug ethambutol (MIC 6.25 μg mL −1 ).